Wild flowers of Lebanon - Nehmeh, Mustapha
Lebanon has a particulary plentiful, rich and varied flora. Considering its area, it has more species of wild flowers than any country in Europe.
Contents, glossary, bibliography, index.
Keywords: Recherche scientifique; Botanique